A política de currículo do Programa de Educação Cidadã Integral para o atendimento de adolescentes e jovens em cumprimento de medidas socioeducativas - Honorato, Rafael Ferreira de Souza (2022)
This thesis has as its object the curricular policy of the Window for the Future program, instituted by Decree No. 37,505 of July 18, 2017. I objectto analyzing the curriculum policy of the Program of Integral Citizen Education for Young People in Compliance with Socio-Educational Measures in the Socio-Educational System of Paraíba. To this end, I prioritized post-structural and post-foundational theoretical-methodological assumptions, moving away from an analytical model of curriculum policies centered on state control, recognizing the complexity of the political process, from the Continuous Policy Cycle (BOWE; BALL, BALL, 2010 GOLD, 1992; BALL, 1994, 2014) and the participation of actors in the production of politics through the Theory of Political Action (BALL; MAGUIRE, BRAUN, 2016). Also in order to break with the structures and forms that seek to limit the translation of politics, I made use of Laclau's Discourse Theory (2011, 2013), Laclau and Mouffe (2015), as well as Mouffe's theorizations (2005, 2011, 2015) to think about the politics and the politics of the curriculum, in a discursive, precarious and contingent perspective, that is, without a single and predefined model of organizing the curriculum, but perceiving it as a result of the articulation of a hegemonic discursive network, however, contingent. As international empirical sources I used the Universal Declaration of Human Rights (ONU, 1948), Convention on the Rights of the Child (ONU, 1989), Minimum Rules for the Administration of Justice of Minors, also called the Beijing Rules (ONU, 1985), Rules for the Protection of Young People Deprived of Liberty, better known as the Havana Rules (ONU, 1990a) and the UN Guiding Principles for the Prevention of Juvenile Delinquency, riyadh rules (ONU, 1990b). Among the national regulations I made use of the Constitution of the Federative Republic of Brazil (BRASIL, 1988), Statute of Children and Adolescents (BRASIL, 1990), Socio-educational Care System (BRASIL, 2006a, 2012), National Guidelines for school care of adolescents and young people in compliance with socio-educational measures (2016), reaching the state documents that were composed of the Program of Integral Citizen Education for the Care of Young People in Compliance with Socio-Educational Measures – Window to the Future (PARAÍBA, 2017a) and the Guidelines of Integral Citizen Schools Socio-Educational – DECIS (PARAÍBA, 2017b) and the interviews conducted with actors who acted in the production of this policy. I conclude by arguing that the curriculum of the Window for the Future program, as a discursive construction, specifically, from the idea of hegemony, is marked by the attempt to project a curriculum designed for the reality of young people who comply with socio-educational measures in deprivation of liberty, in which Integral Education has been instituted as a response of a political-curricular subjectivation to what is unknown to which it seeks to detain, understand, to resath. As a possible responseto the dynamics of socio-educational units, this depends on the interpretative dynamism, which result in an interconnection, multiplicityand hybridizationresulting from the combination of global and local logics, that is, forcing the idea of a curricular homogenization that has been tensionadbythe heterogeneity of the specificities of the socio-educational context.